Residual strength of blast damaged reinforced concrete column - Bao, Xiaoli (2008)
Columns are the key load-bearing elements in framed structures. Exterior columns are probably the most vulnerable structural components in terrorist attacks, and their failure is normally the primary cause of progressive failure. Current knowledge of the post-blast axial load carrying capacity of reinforced concrete columns is limited but could be of great value for predicting the overall performance of buildings, their resistance to progressive collapse, and determining the stability of damaged buildings during search and rescue operations. The principle objective of this research is to study the dynamic responses of reinforced concrete columns under short standoff blast conditions and their postblast axial load carrying capacities. Numerical simulations have been performed using a nonlinear finite element analysis program, LS-DYNA. The finite element (FE) models involved are discussed and verified through correlated experimental studies. The validated FE model was then subjected to simulated blast loads and investigations were carried out on the dynamic responses and residual axial capacities of the columns. An extensive parametric study was carried out on 12 series of columns to investigate the effect of transverse reinforcement ratio, longterm axial load ratio, longitudinal reinforcement ratio, and column aspect ratio on the column responses. The numerical results show that the volumetric ratio of transverse reinforcement has a significant effect on the blast resistance of the reinforced concrete columns. The use of seismic detailing techniques can significantly reduce the degree of direct blast-induced damage and subsequent collapse of the reinforced concrete columns. Comparisons of the deterioration of the axial strength under different axial load ratios indicate that the ratio of residual axial strength is smaller under larger longterm axial load. The effect of axial load ratio is more critical in the case of columns with low transverse reinforcement ratio. The results also show that the ratio of residual axial capacity generally increases with the increase of the longitudinal reinforcement ratio. As for the column aspect ratio, the numerical results indicate that the ratio of residual axial capacity increases with decreasing aspect ratio for columns with high transverse reinforcement ratio. Based on the parametric study results, a formula was derived in terms of various parameters to predict the residual axial capacity ratio based on the mid-height displacement level. An experimental program was devised to simulate the blast effect on the columns and to test the postblast axial capacity of the damaged columns at various degrees of response level. However, due to the break down of the testing equipments and inadequate planning, no satisfactory results were obtained. The results cannot be used for verification of the finite element models. Therefore, the test results will not be discussed in detail in this report. Future experimental investigation of residual axial capacities of the blast damaged reinforced concrete columns is needed to supplement the numerical results used to develop the proposed equation and provide further verification of the finite element model.